Sources of Variation in Clinical Observations: Problems of Teaching and Some Results - Dixon, R. A.; Johnston, S. M. (Methods of Information in Medicine, 1972)
The Wright Peak Flowmeter has proved a useful instrument to demonstrate to fourth year medical students in a three-hour practical class the sources of random and systematic variation arising in biological measurements. A learning effect and both instrument and observer bias including terminal digit preference were analysed by the students using a desk top computer to carry out simple statistical routines. The differing requirements of reproducibility and precision in epidemiological and routine clinical use were discussed.
Keywords: Digit Preference; Peak Flow Meter; Observer Bias; Variation in Biological Measurements; ments.